Incidence of Vibrio metschnikovii in frozen fish products - Sanjeev, S; Varma, P R G; Mukundan, M K (Indian Journal of Fisheries, 2011)
Three hundred and twenty nine samples consisting of frozen fish and fish products collected from processing factories in Kerala and Tamil Nadu were examined for the incidence of Vibrio metschnikovii. This organism was isolated from 16.67% of IQF squid, 8.82% of frozen prawns, 2.38% of frozen squid and 2% of IQF prawns. In general 3.34% of the samples were found to be carriers of V. metschnikovii. All samples of frozen fish fillets, frozen cuttle fish, frozen octopus were found to be free from this organism. Informatioin regarding the incidence of this organism in fish product is scanty. Hence this observation may be relevant to public health considerations of seafood consumption